STUDI ETNOBOTANI TANAMAN PANGAN SUKU JERIENG DI KECAMATAN SIMPANG TERITIP, KABUPATEN BANGKA BARAT - Arieska Camelia; Budi Afriyansyah; Lina Juairiah (Department of Biology, Faculty of Agriculture, Fisheries and Biology, University of Bangka Belitung, 2019)
Plant has many benefit in life, one of example is etnic’s edible food. Jerieng etnic is origin etnic living in the west Bangka district, Bangka Beltung province. Food is everything that grows, lives, has stem, roots, and leaves are eaten directly or need to be processed. The purpose of this research is to record the diversity of food crops (types of edible plant based food, number of species, parts used, processing. This research was conducted from January to November 2018. The research in 13 villages in Simpang Teritip District, West Bangka Regency. Locations include Pelangas Village, Simpang Gong, Air Nyatoh, Pangek, Peradong, Kundi, Air Menduyung, Rambat, Simpang Tiga, Terak Hill, Ibul, Berang, and Mayang. This research aims to do interview and direct observation with the key informant using purposive sampling method. The result of this research found that there are 79 species from 34 families of edible plant-based food in Jerieng etnic. Solanaceae is the most numerous family found including 9 species. The most often used plant part is fruit (39%), meanwhile the less often used plant part is bud (1%). Edible plant based food by Jerieng etnic is divided into two groups, those are processed food and unprocessed food. Example of unprocessed food is local salad (known as “lalapan”) and the processed food such as lempah darat and lempah kuning.